Explaining Variability in Trajectories of Self-Control Using Growth-Curve Modeling: The Effects of Parental Socialization and Victimization - You, Myunghee (Crime & delinquency, 2025)
Many in recent years have found a lack of stability in self-control throughout childhood. We test whether this finding also applies to a non-US sample using six waves of data from a longitudinal survey of South Korean youth ages 13 to 18. We then expand on prior studies by testing whether trajectories of self-control are affected by parental socialization and victimization. Using hybrid growth-curve models, we find a “J-curve” pattern of self-control trajectory, whereby self-control declines in the early years, but then increases in subsequent years. Moreover, parental socialization influences variability of absolute self-control, while victimization affects relative ranking of self-control. We suggest that studies pay attention to the dynamic variability of self-control trajectories over the life course.